2020
DOI: 10.1371/journal.pone.0228849
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and correlates of anal intercourse among female sex workers in eSwatini

Abstract: OPEN ACCESS Citation: Owen BN, M-Giroux M, Matse S, Mnisi Z, Baral S, Ketende SC, et al. (2020) Prevalence and correlates of anal intercourse among female sex workers in eSwatini. PLoS ONE 15(2): e0228849.walk in public places (aOR = 0.46[95%CI:0.25-0.87]). Correlates of AI with inconsistent condom use were similar to those of AI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 55 publications
2
14
1
Order By: Relevance
“…Among the key groups, the lowest prevalence among those infected was found in sex workers (0.53%) and homeless people (0.66%). This is much lesser than the results found in studies in the international sphere, which report 5%-70% prevalence for the first group 7,8 and 16%-28% for populations similar to homeless people in countries such as Ukraine 11 or 7.8%-16.2% in other studies with homeless people in Medellín, Colombia. 19,20 These results lead to the development of three hypotheses.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Among the key groups, the lowest prevalence among those infected was found in sex workers (0.53%) and homeless people (0.66%). This is much lesser than the results found in studies in the international sphere, which report 5%-70% prevalence for the first group 7,8 and 16%-28% for populations similar to homeless people in countries such as Ukraine 11 or 7.8%-16.2% in other studies with homeless people in Medellín, Colombia. 19,20 These results lead to the development of three hypotheses.…”
Section: Discussioncontrasting
confidence: 67%
“…[4][5][6] Among sex workers, the prevalence has been 5% -70%, with a high co-infection of syphilis (5%), chlamydia (8%) and gonorrhoea (2%). 7,8 In persons deprived of liberty have been reported prevalence as low as 0.47% or 2-10 times higher than the general population. 9,10 In homeless was 17%, with heavy alcohol and injection drug use.…”
Section: Introductionmentioning
confidence: 99%
“…Condom use during heterosexual AI was generally low among FSWs and among some men who have sex with men and women (MSMW) populations with prevalence estimates ranging from about 3% to about 70% 18 , 19 , 21 , 23 , 24 , 25 , 27 , 30 , 31 , 32 , 34 , 35 compared to studies reporting heterosexual AI among men and women in the general population whose estimates were over 90% 20 , 26 , 28 , 29 . Studies focusing on men and women in the general population showed that men generally used condoms during AI more than women 17 , 20 .…”
Section: Resultsmentioning
confidence: 93%
“…The prevalence estimates for heterosexual AI ranged from 1.1% among 501 men who have sex with men and women (MSMW) 25 to 59% among 488 female sex workers (FSWs) 31 . Eight studies reported HIV prevalence and or incidences of participants 17 , 20 , 21 , 23 , 27 , 29 , 35 , 36 . The participants' HIV status and their relationship with AI practices was however noticed in half of the 8 studies 17 , 20 , 35 , 36 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation